Moment istiny . Moment istiny . Moment of Truth . Момент истины - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with the Vive-Premier of the Russian Federation Egor Gaidar. Featured in the program: Gaidar, Egor Timurovich (First Deputy Prime Minister of the Russian Federation) Contributors: Karaulov, Andrei (Anchor) Series description: TV show hosted by Andrei Karaulov, where he interviewed prominent politicians, writers, actors, and artists. The program was first aired on September 14, 1992 on the RTR Channel. Интервью с первым заместителем председателя правительства Российской Федерации Егором Гайдаром. В программе участвуют: Гайдар, Егор Тимурович (Первый заместитель председателя Правительства Российской Федерации) Создатели: Караулов, Андрей (Ведущий/Ведущая) Описание серии: Авторская программа Андрея Караулова, включает интервью с политиками, писателями, артистами, деятелями культуры. Программа впервые вышла 14 сентября 1992 года на канале РТР.